1980
DOI: 10.1002/spe.4380100905
|View full text |Cite
|
Sign up to set email alerts
|

A process oriented simulation model specification and documentation language

Abstract: We present a language for specifying and documenting discrete event simulation models, designed to facilitate communication during model design, implementation and maintenance. The systems from which models are developed are viewed as collections of communicating elements. Each element is specified separately in a module consisting of attributes, axioms and a scenario. The model's specification consists of each model element's specification and some systemwide attributes and axioms. Synchronization among model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Later it was discovered that not only the implementation phase but also the model specification and documentation phases need some supporting tools. Consequently, simulation model specification and documentation languages (SMSDL) were developed [Frankowski/Franta 1980]. Such languages enhance the stepwise refinement technique and may typically be transformed automatically into standard simulation languages (e.g.…”
Section: Technical Articlementioning
confidence: 99%
“…Later it was discovered that not only the implementation phase but also the model specification and documentation phases need some supporting tools. Consequently, simulation model specification and documentation languages (SMSDL) were developed [Frankowski/Franta 1980]. Such languages enhance the stepwise refinement technique and may typically be transformed automatically into standard simulation languages (e.g.…”
Section: Technical Articlementioning
confidence: 99%
“…Kleine describes an SMSDL which, by progressive refinement, is intended to lead to executable Simscript programs [23]. Frankowski and Franta propose a process (and Simula) oriented SMSDL [14]. As with Kleine, a specification evolves into an implementation; the same language is used for both.…”
Section: Related Workmentioning
confidence: 99%
“…Our approach is to construct a model specification in a formal language which can be analyzed for diagnostic purposes and which can be transformed through additional analysis into an efficient model implementation (probably in a different language). Several authors have suggested the process concept [4,14,221 or Simscript's entity-attribute-set approach [27] as a basis for modeling methodologies. While neither provides a theory supporting the simulation process, both provide powerful representational and conceptual tools for model specification.…”
Section: Related Workmentioning
confidence: 99%
“…Languages can be used that are self-documenting, that is, they are comprehensive to the user without additional information [5,11,21], This feature is a further enhancement of a simulation language, for it allows the user the opportunity to become wellversed in the language with a minimum amount of training time. Access to an external database is of value to some users [17].…”
Section: Evaluation Criteriamentioning
confidence: 99%